2001
DOI: 10.1109/20.947052
|View full text |Cite
|
Sign up to set email alerts
|

Batch-type millimeter-size transformers for miniaturized power applications

Abstract: Abstract-We have developed a novel batch-type technology for making three-dimensional (3-D) millimeter-sized transformers for ultrasmall low-power (0.1 to 1 Watt) applications. The technology uses the 3-D micropatterning of ferrite wafers by powder blasting to form the magnetic cores of the inductive devices, and combines these cores with electrical windings made by flex-foil printed circuit board technology. Microfabrication and assembly of the parts can be done in a batch process on a wafer/foil level, openi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…With increase in Ferrous ions at higher temperature by controlling its state through oxidation, Ni-Zn and Mn-Zn ferrite can also provide numerous power supplies at low as well as high temperature [42]. Miniaturization also required in such area in order to compete with demand of integrated thin films around 200 o C. Therefore, a new method for synthesizing transformer can also be given with the help of such devices [43].…”
Section: (C) Powermentioning
confidence: 99%
“…With increase in Ferrous ions at higher temperature by controlling its state through oxidation, Ni-Zn and Mn-Zn ferrite can also provide numerous power supplies at low as well as high temperature [42]. Miniaturization also required in such area in order to compete with demand of integrated thin films around 200 o C. Therefore, a new method for synthesizing transformer can also be given with the help of such devices [43].…”
Section: (C) Powermentioning
confidence: 99%
“…A different method based on a batch-fabrication method of 3D transformers and inductors has also been proposed [37]. The magnetic core is made of two half magnetic pieces and a printed circuit board (or flexi foil) carrying the electric windings around the core.…”
Section: 3mentioning
confidence: 99%
“…In [1], Gardner et al showed that a thin Co-Zr-Ti film provide even higher saturation and lower coercive field strengths than Ni-Fe. Other published magnetic cores were cast ferrite cores [4] [5] or, as a non-integrated alternative, assembled amorphous magnetic ribbons [6].…”
Section: Introductionmentioning
confidence: 99%